2002
DOI: 10.1097/00043426-200211000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Home Management of Pain in Sickle Cell Disease: A Daily Diary Study in Children and Adolescents

Abstract: Pain went untreated on a modest number of days, and many patients relied on relatively ineffective single analgesics. Other patients and families appropriately used potent analgesic combinations in a time-contingent and intensity-dependent pattern. This study suggests that recurrent acute pain from SCD can be successfully managed at home with appropriate training and supervision, and suggests several areas for intervention to improve patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
96
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(112 citation statements)
references
References 16 publications
7
96
0
Order By: Relevance
“…A similar study documenting the daily pain of older children with SCD found that while 17 % of patients required admission for pain during the 6-month study period, 40 % experienced at least one episode of pain each month with most episodes lasting one day (Dampier et al 2004 ). A striking range in the days of reported pain was also shown by this study group; a few children reported no days of pain versus a few who recorded pain on >90 % of days (Dampier et al 2002b ). These pain diary studies estimate that while young children (age < ~6 years) with SCD rarely experience pain (Dampier et al 2014 ), older children and adolescents (age ~6-19 years) with SCD have pain more frequently, on one out of every six days (Dampier et al 2002a ).…”
Section: Pain Crisissupporting
confidence: 64%
“…A similar study documenting the daily pain of older children with SCD found that while 17 % of patients required admission for pain during the 6-month study period, 40 % experienced at least one episode of pain each month with most episodes lasting one day (Dampier et al 2004 ). A striking range in the days of reported pain was also shown by this study group; a few children reported no days of pain versus a few who recorded pain on >90 % of days (Dampier et al 2002b ). These pain diary studies estimate that while young children (age < ~6 years) with SCD rarely experience pain (Dampier et al 2014 ), older children and adolescents (age ~6-19 years) with SCD have pain more frequently, on one out of every six days (Dampier et al 2002a ).…”
Section: Pain Crisissupporting
confidence: 64%
“…According to the Pain In Sickle Cell Epidemiology Study adult patients reported SCD pain at home on ϳ 55% of the 31 017 days, 57 whereas children reported SCD pain at home on ϳ 9% of the1515 days surveyed. 58,59 In MSH, at-home analgesics were used for SCD pain on 40% of diary days and 80% of 2-week follow-up periods, with short-acting oxycodone and acetaminophen being the most frequently used analgesics. 21,60 Descriptors and location of pain at home were similar to those during hospitalization but milder.…”
Section: Consequences Of the Acute Painful Crisismentioning
confidence: 99%
“…3 Dampier et al studied children and adolescents (ages 6 -21 years) with SCD for a total of 18,377 days, and found less frequent, but still surprisingly common pain; those studied reported 514 distinct SCD pain episodes occurring over 2592 days and 2326 nights. 4 In a related report, children and adolescents reported SCD pain alone 8.4% of the time (1515 d), whereas other pain occurred 2.7% of the time (490 d), and both SCD and other pain 5.7% of the time (1041 d). 5 These results show that acute pain is definitely the hallmark of SCD, but that chronic pain occurs far more often than was previously realized.…”
mentioning
confidence: 95%